DESENVOLVIMENTO DE TECNOLOGIA LÚDICA PARA CRIANÇAS E SUAS FAMÍLIAS NO PERÍODO PRÉ-CIRÚRGICO - Rodrigues, Flaviana Stock (2024)
The childhood have been constructo in a longo f centuries, without consider in the most of times, the particularities of child audiences. Beyond the historical Evolution and the social place of child. The care work and healthy Tecnology for these group, still represent progression at the moment. Seems like with the children emotional conditions, highliging the relations feelings of them. Pourpose: Develop a children book as a ludic educational resource based on a vídeo “DaviXDodói”(DavidXInjurys) destined to a pre surgery child procedure and their families. The books purpose miltigate tensions and anxieties associated with de surgery process. Giving a support emotional and informative tool, adapt to a sensitive children be haviour condition. Methodology: Talkin about a qualitative exploratory of a part of a understanding of the experiences and childrens necessities and their families in the accord of the surgery process. By the integrative literature review and a post development of a childrens book. The matter that guide the serch of integrative literature review, was? Whats the perception of the parentes emotional conditions during the pre surgery period of thein children. For the identification, selection and classification of the relevant study. A twoof independent evaluatons conducting the process following the guidance os preferred reportaing itens for systematic reviews and meta-analises. The second phase of the search is the publishing of the children´s book (DaviXDodói) DaviXInjury, that breaking though a structure way and contemplate tem phases which the top five have already been completed initially the complications phase contexto, have been envolved the carefully reception of the texts and illustrations, in addition to a QR Code cretion that allow the accessof a ludic vídeo integrated to the book. The layout and design were developed to maximaze the visual impact and easy Reading. A innovation aspect of this Project was the multimidia elements of integration with the additions of QR Code that allow the access of a ludic vídeo. The review and the text edition composed the fourth phase. The fifht phase envolved the publishing of the first versionof the book and its appreciation for a masters Commitee marking a moment relevan in a validations contente. The results: the selection of the studies for this research includes six empirical works originated in Brazil encompassing qualitative and quantitative methods. The analysis of the relatives perseptions of the prepare, before the Pediatrician surgery procedure reveal a consistance faillure on the informations and instructions provided to the parentes and their children. The parentes reports usually surrouds the stress experience, anxiety, fean, restressnes reported before the surgery procedure and physical well beyng of the children, enduring a period that precedes the surgery. Just the children book developed contain twelve pages with illustrations and texts boxes take from DaviXDodói (DavidXInjury)vídeo. And adapted to a capital letter, clearly ad straight. The QR Code readers guide to the ludic vídeo DavidXInjury. The final consideration: this study reveals to be possible a children books creation with pre surgery instructions. With the strenqhen bonos purpose and reduce bad feelings increase into this time, as accessible contentes, ludic, criative, didactics, the book might be a powerful resorce in a regular health education as a promotion strategy of health in a hospital contexto. Impact and applicability of technical product: the resulting book, available in digital media and printed book, detined to be a free resource for families and children facing surgery procedure. Accord to the intention of promote emotional support, relief the tensions and give the surgery experience in pleasent. The printed book available a QR Code that allow the vídeo access. Beyund that, the digital medias book allow the dirtibution more easing to the hospitals and health institutions of a lot differentplaces to a open wide people, this approach submit the importance of thechnology as emotional support and educational, open the new horizons for the children preparations to the medical interventions.